2021
DOI: 10.1093/asj/sjaa395
|View full text |Cite
|
Sign up to set email alerts
|

Age and Body Mass Index Affect Patient Satisfaction Following Reduction Mammoplasty: A Multicenter Study Using BREAST-Q

Abstract: Background Reduction mammoplasty effectively improves quality of life for women with macromastia. However, little is known whether surgical- or patient-related factors affect satisfaction. Objective The authors sought to investigate factors associated with altered patient satisfaction following reduction mammoplasty. Methods A cross-section study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Research on the relation between age and BMI on BREAST-Q scores following reduction mammoplasty found similar results and concluded that breast satisfaction decreased with higher BMI and was higher among older women. 26 This could indicate that younger women are more insecure and more occupied with the appearance of their breasts in relation to finding a partner and/or settling with a family whereas older women already have acquired this situation and now have other aspects to be more bothered about, such as their facial appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the relation between age and BMI on BREAST-Q scores following reduction mammoplasty found similar results and concluded that breast satisfaction decreased with higher BMI and was higher among older women. 26 This could indicate that younger women are more insecure and more occupied with the appearance of their breasts in relation to finding a partner and/or settling with a family whereas older women already have acquired this situation and now have other aspects to be more bothered about, such as their facial appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 24,27 reported preoperative BREAST-Q scores only, 4 studies 20,23,25,26 reported postoperative scores only, and 8 studies 14–19,21,22 reported both preoperative and postoperative scores. The time between reduction and completion of the postoperative BREAST-Q scale varied across articles from less than 3 to 12 months postoperatively, with data not reported from 6 of 14 studies 16,20,23–26 . The length of follow-up time across articles ranged from 6 weeks to 10 years postoperatively, with data not reported from 4 of 14 studies 16,19,24,26 .…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used pedicle was superomedial (50.9%, 532/1046), whereas the inferior pedicle was used in 19.8% (207/1046) of the operations. Two articles 19,27 did not differentiate between superomedial/medial and superior/superolateral pedicles and were therefore omitted from overall estimations of prevalence, resulting in 8 of 14 studies included in this estimation 14,17,18,20,22,23,25,26 . However, these two studies were still included in subsequent linear regressions for other pedicle types, which were specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations